2019
DOI: 10.1021/acsami.9b08389
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Rigidity-Reinforced SiOx Anodes with Stabilized Performance Using an Aqueous Multicomponent Binder Technology

Abstract: Three-dimensional (3D) rigidity-reinforced SiO x anodes are prepared using the aqueous multicomponent binders to stabilize the performances of lithium-ion batteries. Considering an elastic skeleton, adhesiveness, electrolyte absorption, etc., four kinds of binders [polyacrylamide (PAM), poly­(tetrafluoroethylene) (PTFE), carboxymethyl cellulose, and styrene butadiene rubber (SBR)] are selected to prepare aqueous multicomponent binders. The SiO x anodes with the binder PAM/SBR/PTFE (PSP) exhibit a 3D rigidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…For Alg binder, the formed interchains between Alg binder and Si nanoparticles are mainly hydrogen bonding that is generated from carboxylic acid and hydroxyl groups, and this interchain force would be easily broken when facing to the huge volume changes of Si particles, which may result in mechanically fractured sites in the Si electrode and degrade battery performance. [35] In addition, the Si@AlgÀ Zn-PBAs electrode reaches a discharge capacity of 2903.3, 1609.5, 898.5 and 40.9 mAh g À 1 at a current density of 0.42, 2.1, 4.2 and 8.4 A g À 1 , respectively, which is much higher than that of Si@Alg and Si@AlgÀ Zn electrode (Figure 5e). This improved rate capacity may be resulted from the improved ionic conductivity of the AlgÀ Zn-PBAs binder.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…For Alg binder, the formed interchains between Alg binder and Si nanoparticles are mainly hydrogen bonding that is generated from carboxylic acid and hydroxyl groups, and this interchain force would be easily broken when facing to the huge volume changes of Si particles, which may result in mechanically fractured sites in the Si electrode and degrade battery performance. [35] In addition, the Si@AlgÀ Zn-PBAs electrode reaches a discharge capacity of 2903.3, 1609.5, 898.5 and 40.9 mAh g À 1 at a current density of 0.42, 2.1, 4.2 and 8.4 A g À 1 , respectively, which is much higher than that of Si@Alg and Si@AlgÀ Zn electrode (Figure 5e). This improved rate capacity may be resulted from the improved ionic conductivity of the AlgÀ Zn-PBAs binder.…”
Section: Resultsmentioning
confidence: 89%
“…Specifically, the specific discharge capacity of the Si@Alg and Si@Alg−Zn electrode after 200 cycles at 0.84 A g −1 decrease to 890.9 mAh g −1 with a capacity retention rate of 44.07% and 1152.3 mAh g −1 with a capacity retention rate of 58.08%, respectively. For Alg binder, the formed interchains between Alg binder and Si nanoparticles are mainly hydrogen bonding that is generated from carboxylic acid and hydroxyl groups, and this interchain force would be easily broken when facing to the huge volume changes of Si particles, which may result in mechanically fractured sites in the Si electrode and degrade battery performance [35] . In addition, the Si@Alg−Zn‐PBAs electrode reaches a discharge capacity of 2903.3, 1609.5, 898.5 and 40.9 mAh g −1 at a current density of 0.42, 2.1, 4.2 and 8.4 A g −1 , respectively, which is much higher than that of Si@Alg and Si@Alg−Zn electrode (Figure 5e).…”
Section: Resultsmentioning
confidence: 99%
“…[15] Junmin Nan et al developed three-dimensional rigidity-reinforced SiO x anodes using the multicomponent binder. [16] Lin et al utilized a three-in-one design strategy to prepare all-integrated SiO x anode with high mass loading. [17] However, simply tuning mechanical properties of binders cannot fully address the existing issues as nonconductive binders are unable to perform as a well-connected electron transport network between active materials.…”
Section: Doi: 101002/smll202102256mentioning
confidence: 99%
“…[9,10] In addition to CMC and SBR water-based binders, it was found that polyacrylic acid (PAA) and polymers with similar structures were used to prepare the anode plate of LIBs instead of CMC and SBR. [11][12][13] The carboxyl groups in PAA and hydroxyl groups on the surface of anode active material can form hydrogen bonds, which can increase the slurry dispersion, adhesive strength, and cycle lifespan. [14][15][16][17] The aqueous PAA binders also have the advantages of environmental protection and low cost, so PAAs, related polymers, and their composites have recently been extensively developed as graphite anode binders.…”
Section: Introductionmentioning
confidence: 99%
“…However, from the perspective of practical application, the compaction density of the plate after the calendering treatment is low, and the low‐temperature discharge performance is not ideal [9,10] . In addition to CMC and SBR water‐based binders, it was found that polyacrylic acid (PAA) and polymers with similar structures were used to prepare the anode plate of LIBs instead of CMC and SBR [11–13] . The carboxyl groups in PAA and hydroxyl groups on the surface of anode active material can form hydrogen bonds, which can increase the slurry dispersion, adhesive strength, and cycle lifespan [14–17] .…”
Section: Introductionmentioning
confidence: 99%